Brine-filled MXene “Sandwich” system for synergistically enhanced electrochemical energy storage and solar desalination - Bowen Liu; Xuedong He; Yawei Yang; Yuyao Shen; Yihong Liu; Qi Zhao; Xinye Xu; Mo Zhou; Tianyi Wang; Wenxiu Que (Chemical Engineering Journal, 2026)

Energy-force coupling in interfacial solar vapor generation: A pathway to sustainable salt management - Yihong Liu; Yawei Yang; Bowen Liu; Qi Zhao; Yuyao Shen; Mengyuan Qiang; Yong Ma; Wenxiu Que (Desalination, 2025)

Low vaporization enthalpy hydrogels for highly efficient solar-driven interfacial evaporation - Qi Zhao; Yawei Yang; Benxin Zhu; Zuyi Sha; Hui Zhu; Zhixin Wu; Fahad Nawaz; Yumeng Wei; Lingdi Luo; Wenxiu Que (Desalination, 2023)

The cyclin dependent kinase subunit Cks1 is required for infection‐associated development of the rice blast fungus Magnaporthe oryzae - Xiaofeng Yue; Yawei Que; Shuzhen Deng; Lin Xu; Miriam Oses‐Ruiz; Nicholas J. Talbot; Youliang Peng; Zhengyi Wang (Environmental Microbiology, 2017)
Summary Cell cycle regulation is pivotal for proper cell division and cellular differentiation in eukaryotic cells. The central regulators that govern eukaryotic cell cycle progression are cyclin‐dependent kinases (CDKs) and their partners. Here, we report that Magnaporthe oryzae CKS1 encodes a cyclin‐dependent kinase subunit, which plays a significant role in regulation of plant infection. We demonstrate that CKS1 is a functional homolog of CKS1 / SUC1 and can physically interact with the CDK protein Cdc28, and Som1, a downstream regulator of the cyclic AMP‐dependent Protein Kinase A pathway. CKS1 deletion mutants are severely impaired in hyphal growth, sexual reproduction, melanin pigmentation and conidiogenesis. Cks1 mutants are able to form appressoria from hyphal tips, but these are unable to re‐polarize, and rice infection is impaired. CKS1 also affects chitin and glucan synthase activity during cell wall differentiation and fungal hydrophobin function. CKS1 , therefore, encodes a conserved CDK‐binding partner, essential for appressorium‐mediated plant infection by the rice blast fungus.